Revisiting Thorpe scale analysis and diapycnal diffusivities in Drake Passage - Park, Young-Hyang; Durand, Isabelle; Lee, Jae-Hak; Provost, Christine (Frontiers in Marine Science, 2024)
Ship heave effects in the swell-prevalent Southern Ocean induce frequent false overturns in density profiles, and conventional Thorpe scale analysis leads to unrealistically large diapycnal diffusivities. Another critical factor causing large positive biases in Thorpe scale analysis concerns the Ozmidov to Thorpe scales ratio  often considered constant and equal to 0.8. A revised Thorpe scale analysis is proposed with an innovative segment-by-segment approach to circumvent heave-induced false overturns together with best-fitting  functions to Diapycnal and Isopycnal Mixing Experiment in the Southern Ocean (DIMES) data, which yields realistic diffusivities in the Drake Passage region. The revised Thorpe scale method applied to a finely-resolved CTD section across the Drake Passage yields typical diffusivities of O (10-5-10-3 m2 s-1), with the largest values being preferentially concentrated close to the bottom at major circumpolar fronts, consistent with nearby DIMES microstructure observations. In the southern Drake Passage the method highlights a middepth (500-1500 m) mixing maximum of 10-4-10-3 m2 s-1 in the Lower Circumpolar Deep Water (LCDW) layer due to large intrusions of Warm Deep Water (a cold/fresh variety of LCDW) of Weddell Gyre origin. The inferred middepth mixing maximum in intrusive regions, which is associated with isopycnal eddy stirring rather than caused by internal waves or double diffusive mixing, supports the short-circuiting paradigm of meridional overturning circulation in the southwestern Scotia Sea region and has important climatic implications in a warming climate.